Developing a Modern Capstone Course for Technology Management Executive Education Programs: An Evolutionary Process - Ziv, Nina D. (Senate Hall Academic Publishing, 2007)
The Capstone course in technology management executive education programs plays a key role in bringing together various aspects of the curriculum and providing students with a framework for developing their final projects. This article details the evolution of the Capstone course at Polytechnic University in New York City over a six year period. During this time, the faculty teaching the course introduced a series of innovations including the development of themes which contextualized the course, a bi-modal structure which focused on the individual as well as on team projects, and a laboratory-like environment which enabled both faculty, participants and industry professionals to engage in a continual dialogue about the major challenges confronting technology managers in the current business environment.
Keywords: Capstone; executive education; technology management; Polytechnic University; innovation